Cyperus Rotundus L. Phenols Extracts Enhance the Anticancer Effect of Oncolytic Newcastle Disease Virus on Digestive System Neoplasms - Ahmed Majeed Al-Shammari (Journal of Global Pharma Technology, 2016)
This study created novel cancer therapy consist of a combination of Secondary metabolites compound (Phenols) extracted from Cyperus rotundus L. and oncolytic Newcastle disease virus (NDV) which showed cytotoxic activity against different cancer cell lines in vitro. Moreover, it is safe and less toxic on normal cell lines. Three cancer cell lines were used, esophagus cancer cell line (SKG), mouse hepatocellular carcinoma cell line (HC), Human rectal cancer cell line (HRT), and normal cell line Rat Embryo Fibroblast (REF). MTT cell viability assay was used and analyzed for possible synergism using the Chou-Talalay analysis method. In vitro study showed that combination therapy of NDV with Phenols extract had enhanced synergistic anticancer activity on all cancer cell lines tested. Moreover, combination therapies showed antagonism and less cytotoxic effect on normal REF cell line.Keywords: Cancer cell line, Combination therapy, Newcastle virus, phenols, Cyperus rotundus.